Critical assessment of the challenges faced by ZIPA in ensuring investors’ compliance to intended investment - Juma, Faraji S (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirements for award o Master’s Degree of Law in Commercial Law (LL.M. CM.) of Mzumbe University